Flame Retardant Polypropylene Composites with Low Densities - Pérez, Nerea (Materials (Basel), 2019)
Polypropylene (PP) is currently widely used in areas requiring lightweight materials because of its low density. Due to the intrinsic flammability, the application of PP is restricted in many conditions. Aluminum trihydroxide (ATH) is reported as a practical flame retardant for PP, but the addition of ATH often diminishes the lightweight advantage of PP. Therefore, in this work, glass bubbles (GB) and octacedylamine-modified zirconium phosphate (mZrP) are introduced into the PP/ATH composite in order to lower the material density and simultaneously maintain/enhance the flame retardancy. A series of PP composites have been prepared to explore the formulation which can endow the composite with balanced flame retardancy, good mechanical properties, and low density. The morphology, thermal stability, flame retardancy, and mechanical properties of the composites were characterized. The results indicated the addition of GB could reduce the density, but decreased the flame retardancy of PP composites at the same time. To overcome this defect, ATH and mZrP with synergetic effect of flame retardancy were added into the composite. The dosage of each additive was optimized for achieving a balance of flame retardancy, good mechanical properties, and density. With 47 wt % ATH, 10 wt % GB, and 3 wt % mZrP, the peak heat release rate (pHRR) and total smoke production (TSP) of the composite PP-4 were reduced by 91% and 78%, respectively. At the same time, increased impact strength was achieved compared with neat PP and the composite with ATH only. Maintaining the flame retardancy and mechanical properties, the density of composite PP-4 (1.27 g·cm(−3)) is lower than that with ATH only (PP-1, 1.46 g·cm(−3)). Through this research, we hope to provide an efficient approach to designing flame retardant polypropylene (PP) composites with low density.